Efficacy of Aloe Vera Hydrogel in Inhibition The Growth of Campylobacter rectus and Provetella intermedia Bacteria - Chandra Susanto; Member Reni Purba; Ridha Mahrani; Ramayani Efendi (HM Publisher, 2021)
Introduction: Campylobacter rectus and Provetella intermedia bacteria as the main etiology causes of periodontal disease. One of the locally synthesized antimicrobials that is widely used for the treatment of periodontitis is Chlorhexidine, however this drug has side effects when used continuously. To overcome this, an alternative periodontitis therapy with medicinal plants is needed. This study aims to determine the effectiveness of hydrogel Aloe vera antibacterial concentrations of 2.5%, 5%, 10% and 20% in the bacteria Campylobacter rectus and Provetella intermedia. Methods: This study was a laboratory experimental study with posttest only control group design in vitro. The samples were Campylobacter rectus and Provetella intermedia. The number of groups in this study was six. The sample size was determined by Federer's formula and obtained four replications for each group. Data collection by measuring the inhibition diameter using a slide caliper. Data were analyzed using oneway ANOVA and posthoc LSD. Results: The results showed that there was a difference in the diameter of the hydrogel Aloe vera inhibition with a concentration of 2.5%, 5%, 10%, 20% and a positive control for Campylobacter rectus and Provetella intermedia bacteria. Conclusion: This study concluded that there is an antibacterial effectiveness of hydrogel Aloe vera in concentrations of 2.5%, 5%, 10% and 20% on Campylobacter rectus and Provetella intermedia bacteria.